Ribosome Inactivating Proteins from an evolutionary perspective. (15th September 2017) - Lapadula, Walter Jesús; Ayub, Maximiliano Juri
Abstract: Ribosome Inactivating Proteins (RIPs) are rRNA N -glycosidases that inhibit protein synthesis through the elimination of a single adenine residue from 28S rRNA. Many of these toxins have been characterized in depth from a biochemical and molecular point of view. In addition, their potential use in medicine as highly selective toxins is being explored. In contrast, the evolutionary history of RIP encoding genes has remained traditionally underexplored. In recent years, accumulation of large genomic data has fueled research on this issue and revealed unexpected information about the origin and evolution of RIP toxins. In this review we summarize the current evidence available on the occurrence of different evolutionary mechanisms (gene duplication and losses, horizontal gene transfer, synthesis de novo and domain combination) involved in the evolution of the RIP gene family. Finally, we propose a revised nomenclature for RIP genes based on their evolutionary history. Highlights: Ribosome Inactivating Proteins are widely distributed across species. The RIP domain originated before the divergence of the three life domains. The RIP domain has become fused to different partner domains or short sequences leading to the extant AB, AC and AD RIPs. RIP genes from Metazoa are derived from a single Horizontal Gene Transfer event.